Impact of Circadian Disruption on CART mRNA Expression in Nucleus Accumbent: Insights from Constant Light Exposure and Wheel-Running Activity in Rats - Mohseni, Fahimeh; Vahedifar, Afsaneh; mohammadi, shima; Garmabi, Kia; Bakhtazad, Atefeh; Garmabi, Behzad (Shahroud Journal of Medical Sciences, 2025)
Background: Cocaine Amphetamine Related Transcript (CART) is expressed in the nucleus accumbens (NAc), a region that serves as extra-SCN circadian oscillators. This study examined whether CART mRNA in the NAc follows a diurnal rhythm and how circadian disruption affects its expression. Methods: Rats (n=28) were monitored for 30 days in a 12:12 light-dark cycle (LD). On day 30, 14 rats were sacrificed (7 in the morning, 7 in the evening). The remaining rats (n=14) were exposed to constant light (LL) from day 30 to day 60 and then sacrificed (7 in the morning, 7 in the evening). CART mRNA levels were measured via real-time PCR. Results: In the LD group, CART mRNA was higher in the evening than in the morning (P-value<0.001). In the LL group, evening levels remained elevated but were reduced compared to LD (P-value<0.01). Morning mRNA levels in the LL group were lower than in LD (P-value<0.05). Conclusions: Constant light exposure downregulated CART mRNA, suggesting impaired circadian regulation in the NAc. This disruption may alter neurochemical signaling, affecting behavioral and mood-related processes. The findings highlight CART’s role in circadian coordination and its susceptibility to rhythm disturbances, which could influence mood and activity patterns.